Experimental Social Stress: Dopaminergic Receptors, Oxidative Stress, and c-Fos Protein Are Involved in Highly Aggressive Behavior - Felippe, Renata M.; Oliveira, Gabriel M.; Barbosa, Rafaela S.; Esteves, Betina D.; Gonzaga, Beatriz M. S.; Horita, Samuel I. M.; Garzoni, Luciana R.; Beghini, Daniela G.; Araújo-Jorge, Tânia C.; Fragoso, Viviane M. S. (Frontiers in Cellular Neuroscience, 2021)
Aggression is defined as hostile behavior that results in psychological damage, injury and even death among individuals. When aggression presents itself in an exacerbated and constant way, it can be considered escalating or pathological. The association between social stress and the emergence of exacerbated aggressiveness is common and is suggested to be interconnected through very complex neurobiological factors. For example, alterations in the expression of the dopaminergic receptors D1 and D2, reactive oxygen species (ROS) and the c-Fos protein in the cortex have been observed. Our objective was to analyze which factors are involved at the neurobiological level in the highly aggressive response of Swiss Webster adult male mice in a vivarium. In this work, we investigated the relationship among dopaminergic receptors, the production of ROS and the expression of c-Fos. Mice with exacerbated aggression were identified by the model of spontaneous aggression (MSA) based on the grouping of young mice and the regrouping of the same animals in adulthood. During the regrouping, we observed different categories of behavior resulting from social stress, such as i) highly aggressive animals, ii) defeated animals and iii) harmonic groups. To evaluate the dopaminergic system and the c-Fos protein, we quantified the expression of D1 and D2 dopaminergic receptors by Western blotting and fluorescence immunohistochemistry and that of the c-Fos protein by fluorescence immunohistochemistry. The possible production of ROS was also evaluated through the dihydroethidium (DHE) assay. The results showed that aggressive and subordinate mice showed a reduction in the expression of the D1 receptor, and no significant difference in the expression of the D2 receptor was observed between the groups. In addition, aggressive mice exhibited increased production of ROS and c-Fos protein. Based on our results, we suggest that exacerbated aggression is associated with social stress, dysregulation of the dopaminergic system and exacerbated ROS production, which leads to a state of cellular oxidative stress. The overexpression of c-Fos due to social stress suggests an attempt by the cell to produce antioxidant agents to reduce the toxic cellular concentration of ROS.